Shear Wave Measurements of the Elasticity of the Ground - Enas Altalhe; Sara Boshah; Hadeel Ayad; Sajida Ali (AlQalam Journal of Medical and Applied Sciences, 2025)
The usage of shear wave speed (Vs) techniques has emerged as a cornerstone in modern-day geotechnical engineering, substantially enhancing the assessment of soil and rock properties. Vs is important for figuring out the dynamic conduct of soils, which is important for assessing their response to seismic events and for the layout of vibration-resistant structures. This paper underscores the pivotal role of Vs measurements in high-stakes infrastructure initiatives, such as bridges, skyscrapers, and nuclear power flowers, where specific information on shear modulus (G), damping ratio (D), and shear wave pace (Vs) is essential. Notably, case research from the 2011 Izmir and 2023 Kahramanmaraş earthquakes illustrates the potential of these techniques to improve seismic layout accuracy using as tons as 40%. The review encompasses several non-intrusive evaluation techniques, inclusive of electric resistivity strategies, floor-penetrating radar (GPR), and seismic trying out, which depend on the generation of mechanical waves. It places precise emphasis on surface wave analysis strategies, inclusive of Spectral Analysis of Surface Waves (SASW) and Multi-Mode Spectral Analysis of Surface Waves (MASW), which give targeted insights into subsurface situations without necessitating excavation Moreover, the integration of laboratory and field techniques, along superior data processing methodologies, has led to widespread improvements inside the accuracy of dynamic soil belongings measurements. The findings of this paper highlight the pressing need for modern strategies to enhance the reliability of geotechnical checks, especially in seismically active regions. This painting aims to contribute to the continuing discourse on optimizing shear wave velocity size techniques and their programs in geotechnical engineering, in the end fostering safer and more resilient infrastructure.